Cigarette smoking impairs nitric oxide-mediated cerebral blood flow increase: Implications for Alzheimer's disease - Noboru Toda; Tomio Okamura (Elsevier, 2016)
Cerebral blood flow is mainly regulated by nitrergic (parasympathetic, postganglionic) nerves and nitric oxide (NO) liberated from endothelial cells in response to shear stress and stretch of vasculature, whereas sympathetic vasoconstrictor control is quite weak. On the other hand, peripheral vascular resistance and blood flow are mainly controlled by adrenergic vasoconstrictor nerves; endothelium-derived NO and nitrergic nerves play some roles as vasodilator factors. Cigarette smoking impairs NO synthesis in cerebral vascular endothelial cells and nitrergic nerves leading to interference with cerebral blood flow and glucose metabolism in the brain. Smoking-induced cerebral hypoperfusion is induced by impairment of synthesis and actions of NO via endothelial nitric oxide synthase (eNOS)/neuronal NOS (nNOS) inhibition and by increased production of oxygen radicals, resulting in decreased actions of NO on vascular smooth muscle. Nicotine acutely and chronically impairs the action of endothelial NO and also inhibits nitrergic nerve function in chronic use. Impaired cerebral blood supply promotes the synthesis of amyloid β that accelerates blood flow decrease. This vicious cycle is thought to be one of the important factors involving in Alzheimer's disease (AD). Quitting smoking is undoubtedly one of the important ways to prevent and delay the genesis or slow the progress of impaired cognitive function and AD.